Fabrication and structural, physical, and nuclear radiation shielding properties for Oxide Dispersion-Strengthened (ODS) alloys through Erbium (III) oxide, Samarium (III) oxide, and Praseodymium (III) oxide into 316L matrix - Guler, Seval Hale; Guler, Omer; Kavaz, E.; ALMisned, Ghada; Albayrak, M. Gokhan; Issa, Bashar; Tekin, H. O. (Elsevier Sci Ltd, 2024)
We report a comprehensive investigation on customization process of Oxide Dispersion-Strengthened alloys through Sm2O3, Pr2O3, and Er2O3 incorporation into 316L stainless steel matrix in terms of a desired enhancement in structural, physical, and nuclear radiation shielding properties. Oxide powders are incorporated into 316L stainless steel powder all with the same purity of 99.5%. These were Erbium oxide (Er2O3), Praseodymium oxide (Pr2O3), and Samarium oxide (Sm2O3). First, X-Ray diffraction and Scanning Electron Microscope/Energy-dispersive X-ray spectroscopy analyses are conducted in order to investigate their physical and structural properties. Next, two different experimental setups are employed using a133Ba and 241Am/Be sources for the measurements of gamma-ray and neutron transmission properties of Oxide Dispersion -Strengthened alloys. The maximum density increment is achieved through Er2O3 compared to other rein-forced oxides. The detector counting value reached its minimum level when a 5% Er2O3 oxide dispersion was introduced into the 316L SS matrix. Similarly, the most significant degree of photon absorption, the highest values of mass attenuation coefficient, lowest half value layer, and most effective atomic number, were all attained by the same sample. Based on the findings derived from the investigation, it can be concluded that incorporating Er2O3 oxide into 316L steel can be considered as a viable option in terms of enhancing the critical properties of Oxide Dispersion-Strengthened alloys for extreme conditions such as nuclear reactors and other similar fields, where the behavioral attributes of the utilized materials are at utmost importance.
Keywords: Oxide Dispersion-Strengthened alloys; Mechanical alloying; XRD; EDX; Gamma-ray; Neutron